Benign adnexal neoplasms of the skin: a 6-year histopathological review - Acosta, José G. García; Ramírez, Marissa D. Quintal (International Journal of Research in Dermatology, 2025)
Background: Tumours of the cutaneous appendages of the skin are a class of benign and malignant dermatological neoplasms, which present special morphological differentiation such as glandular, pilar or sebaceous. Methods: A descriptive, observational, retrospective, and cross-sectional study focused on the histopathological diagnoses corresponding to benign neoplasms of the cutaneous appendages reported in the La Raza National Medical Center, México. For statistical analysis, descriptive statistics were used, with frequency distribution, percentage, mean, median. Results: A total of 8,618 skin biopsy reports were analyzed. Of these, 222 were diagnoses of benign adnexal neoplasms. The prevalence was 2.57%. Of the total, 59.9% occurred in women and 40.1% in men. The median age was 56.9 years; in an age range from 61 to 70 years old. The most frequent anatomical location was the nose with 20.3%, followed by the lower extremities with 18.9%. Neoplasms with apocrine and eccrine differentiation were the most common, representing 55.9% of cases. Poroma was the most common subtype in our study, accounting for 19.37% of cases, followed by pilomatrixomas and trichodiscomas, both accounting for 15.77%. Conclusions: Benign adnexal neoplasms of the skin have a prevalence of 2.57%. They occurred mostly in women aged 61 to 70 years. The most common adnexal tumor was poroma, and the most common location of appearance was the nose.